VALIDITAS MULTIMEDIA INTERAKTIF “AYO LESTARIKAN LINGKUNGAN” PADA MATA PELAJARAN IPAS SISWA KELAS TINGGI SDN 41 MALEWANG KABUPATEN TAKALAR - Fitriana; Ummul Khaeri; Nurhikmah H; Safaruddin; Suryadi Ishak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the validity of the interactive multimedia “Ayo Lestarikan Lingkungan” as a learning medium for the Science and Social Studies (IPAS) subject among upper-grade students at SDN 41 Malewang, Takalar Regency. The media was developed to address the need to improve IPAS learning, which remains dominated by conventional methods, leading to low student engagement and suboptimal comprehension of environmental conservation concepts. The research employed a Research and Development (R&D) approach focusing on the expert validation stage. Instruments consisted of validation sheets from material experts and media experts, assessing content accuracy and visual design quality. Data were analyzed by calculating the average validation scores and categorizing them according to established media feasibility criteria. The results show that the interactive multimedia achieved a valid rating across all evaluation aspects. Media experts reported an overall validity of 91.40%, with several aspects—layout, animation, typography, audio, video, interface, program, and navigation—rated highly valid. Material experts rated the learning aspects, content, and language at 79.63%, categorized as valid. Based on these findings, the developed multimedia is feasible for use as a learning medium to enhance students’ understanding and awareness of environmental conservation. The study implies that integrating interactive multimedia can be an effective alternative for improving the quality of IPAS instruction in elementary schools